Architectural engineering as a profession: report on research leading to a curriculum revision - Parasonis, Josifas; Jodko, Andrej (Journal of Civil Engineering and Management, 2013)
Modern design practice, where an architect works with engineers in a large team, lacks optimisation. Improvement of collaboration between the professions of architecture (A) and structural engineering (SE) would result in more efficient structures. Collaboration can be improved by professionals who have training and/or experience in both professions. The fact is proved by the professionals that either were separately trained in each field, or had integrated training in both fields, or successfully practised on the borderline between A and E. The concept of architectural engineering (AE) appeared in the late nineteenth century, and the profession has increasingly been developing from that time on. The Aim of the research is to develop a competence model (CM) for an AE professional, and scientifically substantiate the subject matter of the undergraduate AE programme. The Scope of the study is the analysis of collaboration issues relating to the civil engineering (CE) and A professions, studies on the development of CM, and development of the study programme curriculum. The authors developed a CM for an AE professional containing essential competences and courses of the curriculum for training of the modern professional proficient in the development of architectural and structural design projects.